STUDENTS ACCEPTANCE OF PORTOFOLIO ASSESSMENT IN AN ENGLISH FOR SPECIFIC ACADEMIC PURPOSE (ESAP) COURSE AT A POLYTECHNIC IN CHINA-REFLECTION ON LECTURER BEST PRACTICES - Qiao Li-Ping; Norkhairi Ahmad (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2022)
Learning portfolio records the dynamic learning process of individual learners as a form of formative assessment.  Portfolio evaluation system has attracted great interest from language educators as  it could train learners  and improve their  language proficiency. This paper set out to explore the potential benefits that could be gained in language learning via the implementation of learning portfolio assessment. This paper uses a case study of the teaching and learning of a course in the major of business English in a vocational college to show the significance of portfolio evaluation system in increasing students interest and their learning autonomy. The students showed positive response via survey questionnaires that registered a mean of 3.90 with all items being recorded above 3.50 and via the structured interviews where the students expressed strong receptiveness to the range of benefits that they could gradually gain via such a dynamic teaching, learning and assessing process. Recorded observations by the author also showed positive signs of development in key areas like learners autonomy, self-confidence, critical thinking and self- reflection abilities. This study has positive implications for the teaching and learning in vocational college and will be useful for educators to take up as a dynamic teaching and learning approach.